Floquet topological insulators. Issue 1 (28th January 2013) - Cayssol, Jérôme; Dóra, Balázs; Simon, Ferenc; Moessner, Roderich
Abstract <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text> Topological insulators represent unique phases of matter with insulating bulk and conducting edge or surface states, immune to small perturbations such as backscattering due to disorder. This stems from their peculiar band structure, which provides topological protections. While conventional tools (pressure, doping etc.) to modify the band structure are available, time periodic perturbations can provide tunability by adding time as an extra dimension enhanced to the problem. In this short review, we outline the recent research on topological insulators in non‐equilibrium situations. Firstly, we introduce briefly the Floquet formalism that allows to describe steady states of the electronic system with an effective time‐independent Hamiltonian. Secondly, we summarize recent theoretical work on how light irradiation drives semi‐metallic graphene or a trivial semiconducting system into a topological phase. Finally, we show how photons can be used to probe topological edge or surface states. (© 2013 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)